Financial Sustainability of Culinary SMEs: Examining the Role of Working Capital and Liquidity in Makassar - Pammai, Asri; Paridy, Andryanus; Todingbua, Manuel August (Master of Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
Small and Medium Enterprises (SMEs) play a crucial role in economic development, particularly in emerging markets such as Indonesia. In Makassar, the culinary sector has become one of the primary drivers of economic activity, yet many SMEs struggle with financial management, particularly in working capital and liquidity management. This study aims to analyze the impact of working capital and liquidity on the performance of culinary SMEs in Makassar. The research employs a quantitative approach, collecting data from 96 SME owners through structured questionnaires. The analysis utilizes Structural Equation Modelling (SEM) with SmartPLS 4. The findings indicate that liquidity has a significant positive effect on SME performance, while working capital does not exhibit a statistically significant impact. This suggests that financial stability, particularly the ability to meet short-term obligations, is crucial for SME sustainability in the culinary industry. However, efficient working capital management alone does not guarantee business success, implying that other factors such as operational efficiency and market strategies may play a more dominant role. These results provide valuable insights for SME owners, policymakers, and financial institutions in formulating strategies to enhance SME growth and resilience. Future research is recommended to explore additional variables that influence SME performance, such as financial literacy, digital transformation, and external funding accessibility.